2017
DOI: 10.1093/toxsci/kfx114
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Differential Responses of Tumor Promotion-Associated Genes and Dysregulation of Novel Long Noncoding RNAs in Constitutive Androstane Receptor-Activated Mouse Liver

Abstract: Xenobiotic agonists of constitutive androstane receptor (CAR) induce many hepatic drug metabolizing enzymes, but following prolonged exposure, promote hepatocellular carcinoma, most notably in male mouse liver. Here, we used nuclear RNA-seq to characterize global changes in the mouse liver transcriptome following exposure to the CAR-specific agonist ligand 1,4-bis-[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP), including changes in novel long noncoding RNAs that may contribute to xenobiotic-induced pathophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 57 publications
7
85
2
Order By: Relevance
“…Sex differences in mouse and human liver are linked to the sex-specific pattern of growth hormone secretion by the pituitary gland [69][70][71]. While we have demonstrated the presence of proximal and distal sex-biased looping in mouse liver, it is not clear how dynamic these loops are in response to factors that dysregulate sexbiased gene expression following alterations in hormone patterns [72] or xenobiotic exposure [60]. In an extreme example of dynamic looping, complete loss of cohesin followed by its reintroduction (achieved by auxin-induced targeted degradation and withdrawal) establishes that virtually all loops are lost after 40 min then regained within an hour of auxin withdrawal [22].…”
Section: Matthews and Waxman -Pagementioning
confidence: 59%
See 2 more Smart Citations
“…Sex differences in mouse and human liver are linked to the sex-specific pattern of growth hormone secretion by the pituitary gland [69][70][71]. While we have demonstrated the presence of proximal and distal sex-biased looping in mouse liver, it is not clear how dynamic these loops are in response to factors that dysregulate sexbiased gene expression following alterations in hormone patterns [72] or xenobiotic exposure [60]. In an extreme example of dynamic looping, complete loss of cohesin followed by its reintroduction (achieved by auxin-induced targeted degradation and withdrawal) establishes that virtually all loops are lost after 40 min then regained within an hour of auxin withdrawal [22].…”
Section: Matthews and Waxman -Pagementioning
confidence: 59%
“…Despite identifying ~1,000 sex-biased binding sites for CTCF or cohesin, the majority are distal from enhancers or genes with known sex bias. Although these distal sites lack any obvious link to sex-biased gene expression in wild type liver, they could have a priming effect and contribute to sex-specific responses to hepatic stressors, such as high fat diet [59] or xenobiotic exposure [60]. Just as short-term feeding of a high fat diet can leave a lasting "epigenetic memory" in the form of epigenetic modifications [61], sex-biased CTCF/cohesin binding sites may prime each sex for differential looping patterns in response to subsequent chemical exposure or dietary stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the PPARA-responsive lncRNAs to lncRNAs responsive to agonist ligands of two other nuclear receptors in mouse liver, namely CAR and PXR (Lodato et al, 2017), identified 8 lncRNAs that are induced by all three nuclear receptors and 11 lncRNAs repressed by all three receptors. Forty five other lncRNAs were induced, or were repressed, in common by PPARA and CAR, and 30 other lncRNAs were either induced or repressed in common by PPARA and PXR (Table S1C).…”
Section: Lncrna Regulation By Ppara Is Highly Tissue-specificmentioning
confidence: 99%
“…Down-regulation of lncRNA lncOb reduces leptin, leading to a leptin responsive form of obesity (Dallner et al, 2019). Other studies found that lncRNAs are regulated during adipocyte differentiation (Yuan et al, 2019a;Yuan et al, 2019b), are expressed in liver in a sex-dependent manner when regulated by growth hormone (Melia et al, 2016;Melia and Waxman, 2019), and can be strongly induced by xenobiotic exposure (Lodato et al, 2017). A compartment-specific transcriptional profiling approach revealed that lncRNA PAXIP1-AS1 regulates pulmonary arterial hypertension by modulating smooth muscle cell function (Jandl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%